Women in HIV cure research: multilevel interventions to improve sex equity in recruitment - Mary E. Grewe; Yuntong Ma; Adam Gilbertson; Stuart Rennie; Joseph D. Tucker (Elsevier, 2016)
Women are underrepresented in HIV cure research. In this paper we discuss the rationale for including women and propose multilevel strategies to improve sex equity in HIV cure research. The inadequate inclusion of women in HIV cure research is concerning for both scientific and ethical reasons. Biological responses to HIV and HIV treatment, as well as social contexts, differ between men and women, and this may affect the efficacy of curative interventions. Strategies for improving sex equity in HIV cure research include addressing eligibility criteria, adapting recruitment strategies, engaging community members early in the research process, and promoting funder policy changes. We conclude by describing the Gender, Race, and Clinical Experience (GRACE) study, which is one example of how women can be effectively recruited into HIV-related clinical trials. While HIV cure research is currently in the early stages, as it continues to develop it is important to mobilise for adequate inclusion of women.